Experimentelle Untersuchungen zum Innengeräusch von Fahrzeugluftreifen - Krauss, Oliver (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2019)
In the toroidal tire cavity, standing waves can occur, leading to very high amplitudes. To investigate the cavity modes, experimental investigations are performed with pulse excitation, on a tire inner-drum test bench and under real operating conditions with a vehicle. At first, fundamental examinations are presented that focus on the identification of cavity modes and on the different system states. In a next step, various excitation mechanisms and important influencing factors are considered.